Філософія права доби постмодерну: людина та її права - Бандура, О.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
Для постмодерна в философии и в философии права является характерным отрицание классического Разума и, соответственно, выработанной мыслителями Просвещения концепции субъекта как целостного и самодостаточного. Этим обусловлено присущее многим постмодернистам отрицание прав человека. Вместе с тем некоторые сторонники постмодерна признают эти права. Такая неоднозначность в определенной степени обусловлена тем, что права человека берутся изолированно от интересов социума. Эти права должны отражать внутреннюю гармонию взаимных связей личности с социумом, что не учитывается постмодернистской философией права в полной мере. One of the main characteristics of the postmodern in philosophy and in legal philosophy consists of a denial
of the classical Mind and accordingly of the Enlightenment conception of subject as integral one. Many
postmodernists deny the concept of human rights. At the same time there are some supporters of the postmodern
who recognize these rights. Basically such the uncertainty is a result of the circumstances that human
rights are viewed separately from the interests of society. These rights must reflect an inside mutual connection
between personality and society. The postmodern legal philosophy does not take it into account to the
full extent.